The Streptococcus milleri group in chronic obstructive pulmonary disease - Navratilova, Lucie; Bardon, Jan; Novotny, Radko; Zatloukal, Jaromir; Jakubec, Petr; Kolek, Vitezslav; Zapalka, Martin; Kopriva, Frantisek; Prochazkova, Petra; Raclavsky, Vladislav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND AND AIMS: S. anginosus, constellatus and intermedius, also known as the Streptococcus milleri group (SMG) are three streptococcal species more frequently detected in cases of invasive disease, abscesses and empyema in particular. Recent research suggests they play a role in exacerbations of cystic fibrosis (CF). Owing to poor recovery on standard culture media and difficult differentiation from non-pathogenic streptococci, SMG may be underdiagnosed in routine settings. We aimed to establish the incidence of SMG in chronic obstructive pulmonary disease (COPD) patients compared to CF patients and to examine possible links of SMG to exacerbations that plays a key role in progression of COPD. METHODS: Altogether, 90 respiratory tract samples of patients suffering from CF or COPD were examined during the period from July 2012 to December 2013. Semi-selective McKay agar was used for primary cultivation of SMG and MALDI TOF MS was used for species identification that was confirmed by biochemical profiling and specific PCR. RESULTS: We confirmed the presence of SMG in CF (17.6% incidence in adult patients) and newly established its presence in COPD (10.3% incidence). In COPD, SMG was detected in 4 cases of acute exacerbations, where no other bacterial pathogen was detected. In 3/4 cases, increased CRP level indicated bacterial infection as a cause of the exacerbation and in all 3 cases, patients recovered during antibiotic treatment. CONCLUSIONS: Our data indicate SMG may act as opportunist pathogens able to cause exacerbations in COPD.
Keywords: Streptococcus intermedius; oportunní infekce; Humans; Sputum; lidé středního věku; Respiratory Tract Infections; chronic obstructive pulmonary disease; Aged; dospělí; Streptococcus constellatus; senioři; lidé; Streptococcus milleri Group; Streptococcus milleri group; streptokokové infekce; Streptococcus anginosus; Streptococcal Infections; Adult; Cystic Fibrosis; Opportunistic Infections; Male; Middle Aged; sputum; infekce dýchací soustavy; chronická obstrukční plicní nemoc; cystická fibróza; skupina Streptococcus milleri; Pulmonary Disease, Chronic Obstructive; mužské pohlaví; Acute Disease; akutní nemoc; cystic fibrosis